Basal Forebrain Volume, but Not Hippocampal Volume, Is a Predictor of Global Cognitive Decline in Patients With Alzheimer's Disease Treated With Cholinesterase Inhibitors - Teipel, Stefan J.; Cavedo, Enrica; Hampel, Harald; Grothe, Michel J.; , Alzheimer's Disease Neuroimaging Initiative; , Alzheimer Precision Medicine Initiative (APMI); Aguilar, Lisi Flores; Babiloni, Claudio; Baldacci, Filippo; Benda, Norbert; Black, Keith L.; Bokde, Arun L. W.; et al. (Frontiers in Neurology, 2018)
Background: Predicting the progression of cognitive decline in Alzheimer’s disease (AD) is important for treatment selection and patient counseling. Structural MRI markers such as hippocampus or basal forebrain volumes might represent useful instruments for the prediction of cognitive decline. The primary objective was to determine the predictive value of hippocampus and basal forebrain volumes for global and domain specific cognitive decline in AD dementia during cholinergic treatment. Methods: We used MRI and cognitive data from 124 patients with the clinical diagnosis of AD dementia, derived from the ADNI-1 cohort, who were on standard of care cholinesterase inhibitor treatment during a follow-up period between 0.4 and 3.1 years. We used linear mixed effects models with cognitive function as outcome to assess the main effects as well as two-way interactions between baseline volumes and time controlling for age, sex and total intracranial volume. This model accounts for individual variation in follow-up times. This analysis was conducted using libraries"lme4" and "lmerTest"in the software platform R Results: Basal forebrain volume, but not hippocampus volume, was a significant predictor of rates of global cognitive decline. Larger volumes were associated with smaller rates of cognitive decline. Left hippocampus volume had a modest association with rates of episodic memory decline. Baseline performance in global cognition and memory was significantly associated with hippocampus and basal forebrain volumes; in addition, basal forebrain volume was associated with baseline performance in executive function. Conclusions: Our findings indicate that in AD dementia patients, basal forebrain volume may be a useful marker to predict subsequent cognitive decline during cholinergic treatment.